Favorable mortality-to-incidence ratios of kidney Cancer are associated with advanced health care systems - Wen-Wei Sung; Shao-Chuan Wang; Tzuo-Yi Hsieh; Cheng-Ju Ho; Cheng-Yu Huang; Yu-Lin Kao; Wen-Jung Chen; Sung-Lang Chen (BMC Cancer, 2018)
Abstract Background The advancements in cancer therapy have improved the clinical outcomes of cancer patients in recent decades. However, advanced cancer therapy is expensive and requires good health care systems. For kidney cancer, no studies have yet established an association between clinical outcome and health care disparities. Methods We used the mortality-to-incidence ratio (MIR) for kidney cancer as a marker of clinical outcome to compare World Health Organization (WHO) country rankings and total expenditures on health/gross domestic product (e/GDP) using linear regression analyses. Results We included 57 countries based on data from the GLOBOCAN 2012 database. We found that more highly developed regions have higher crude and age-standardized rates of kidney cancer incidence and mortality, but a lower MIR, when compared to less developed regions. North America has the highest crude rates of incidence, but the lowest MIRs, whereas Africa has the highest MIRs. Furthermore, favorable MIRs are correlated with countries with good WHO rankings and high e/GDP expenditures (p < 0.001 and p = 0.013, respectively). Conclusions Kidney cancer MIRs are positively associated with the ranking of health care systems and health care expenditures.